Перемещение Halicyclops longispinosus в род Colpocyclops (Crustacea, Copepoda) и первое описание его самцов - Монченко, В.И. (Вестник зоологии, 1978)
Two males of H. longispinosus are described and figured. A very peculiar structure of the mouth parts of this species corresponds to that of the genus Colpocyclops the species is transferred to. The differential diagnoses of both its species (C. dulcis and C. longispinosus comb. nov.) and some additional data of the genus characteristic are given. The genus is endemic for the Western Black Sea limans province of the Ponto-Kaspian brackish region.